Cyber-physical aerodynamic shape optimization of a tall building in a wind tunnel using an active fin system. Issue 220 (January 2022) - Whiteman, Michael L.; Fernández-Cabán, Pedro L.; Phillips, Brian M.; Masters, Forrest J.; Davis, Justin R.; Bridge, Jennifer A.
Abstract: This study explores the use of a cyber-physical systems (CPS) framework for the design and optimization of the aerodynamics of a tall building through aeroelastic boundary layer wind tunnel (BLWT) testing. The framework is a fully-automated combination of traditional experimental wind tunnel testing with numerical optimization strategies to evaluate a wide range of candidate designs both accurately and quickly. In this study, candidate designs are achieved through the physical adjustment of the aerodynamic shape of a multi-degree-of-freedom (MDOF) aeroelastic tall building model. BLWT testing is carried out at the University of Florida Natural Hazard Engineering Research Infrastructure (NHERI) Experimental Facility (EF). The specimen is equipped with an actuation system consisting of a series of individually-controllable slotted fins comprising an active fin system (AFS), which enable precise modifications of the aerodynamic shape of the envelope. The wind-induced building response of the specimen is directly captured using a series of accelerometers and laser displacement sensors. A stochastic optimization algorithm is then employed in the aerodynamic CPS framework to evaluate the fitness of each candidate design based on specified performance criterion related to either occupant comfort or building drift. Optimization results indicate that the CPS framework can reliably achieve the optimal solution which minimizes the response (i.e., horizontal accelerations and lateral displacements) of the aeroelastic specimen. Highlights: Active fin system to adjust a building's aerodynamics. Mechatronic building model with automated control. Automated optimization of a building's aerodynamics in a wind tunnel. Aeroelastic model of a tall building at 1:200 scale. Optimal designs meeting displacement and acceleration constraints.